2002
DOI: 10.1021/nl025703o
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Construction of Nanostructured Porphyrin−Fullerene Electrodes

Abstract: The fabrication of high quality, robust, and photoactive ITO electrodes is reported. Electrostatic and van der Waals interactions have been used for the step-by-step deposition of layers containing a fullerene−porphyrin dyad as the active layer. The new electrodes give rise to improved light harvesting features in the visible, with absorbances as high as 0.2 (i.e., at the Soret band of H 2 P) for a monolayer coverage and IPCEs of 0.38% and 0.6% under anaerobic and aerobic conditions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…The IPCE values are comparable to those of other fullerene-based multilayer photovoltaic cells. [59,60] In addition, the IPCE response extends to 600 nm. This indicates that the photosensitization process originates from the polymer 1/PTEBS junction that both polymers took part in during the photoinduced charge generation process.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…The IPCE values are comparable to those of other fullerene-based multilayer photovoltaic cells. [59,60] In addition, the IPCE response extends to 600 nm. This indicates that the photosensitization process originates from the polymer 1/PTEBS junction that both polymers took part in during the photoinduced charge generation process.…”
Section: à2mentioning
confidence: 99%
“…The multilayers were mainly based on fullerene derivatives as the electron acceptors. [59][60][61][62][63] It has been shown previously that the photocurrent generation and decay in polymer multilayers composed of poly(phenylenevinylene), poly(acrylic acid), poly(allylamine hydrochloride), and fullerene can be fitted to a biexponential function. The multilayer films were regarded as a capacitor in which the charging process corresponds to the photoinduced electrontransfer process.…”
Section: à2mentioning
confidence: 99%
“…Guldi et al reported a unique effect of molecular structure on the efficiency of photoinduced charge separation in LbL films of a porphyrin-fullerene dyad molecule [121] ( figure 11). In that porphyrin-fullerene dyad, porphyrin and fullerene moieties are bridged through a short rigid spacer.…”
Section: Commanded Assemblymentioning
confidence: 99%
“…Successful applications of this technique are in the field of photoinduced electron transfer reactions, where the functional two-dimensional or three-dimensional thin films incorporate photosensitisers, which can generate photoelectrons under light illumination [10][11][12]. It is well known that porphyrins represent an important class of photosensitisers with high extinction coefficients in the visible region.…”
Section: Introductionmentioning
confidence: 99%